THE USE OF GOOGLE JAMBOARD TO IMPROVE STUDENTS’ READING COMPREHENSION - Ari Dwipayanti (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The development of information technology makes technology used in various fields, one of which is education. At first, traditional learning was synonymous with the use of whiteboards, chalk, and markers to facilitate the delivery of material. However, the presence of technology makes learning more interesting for students. Google Jamboard is one of the technologies known as digital whiteboards that can be used to teach English skills. This study aims to determine the use of Google Jamboard as a tool to improve reading comprehension in EFL students. This research is qualitative research using the results of interviews with English teachers who use Google Jamboard as a teaching tool and EFL students. The results of the study show that Google Jamboard can assist teachers in teaching reading comprehension activities to students and is able to provide interactive learning for students.